(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
According to the United Nations, there are one billion people worldwide who are disabled.Being human entails having a limitation. At some time in our lives, we will all become temporarily orpermanently incapacitated. In today’s society, the majority of homes include someone who is disabled.The sensitivity to disability changes throughout time and across populations. Despite recognisedmedical grounds, the disease is seen in Africa as a spiritual retribution. In the West, disability is seen asa natural phenomenon that may be explained by medical concepts. People’s movements and healthsciences have lately recognised and highlighted the role of physical and social barriers in disability.Therefore, This paper focus on the theoretical aspect of the assessment socio-economic and educationalstatus of physically disabled students in INDIA